2016
DOI: 10.1053/j.gastro.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Endocannabinoid System in the Brain–Gut Axis

Abstract: The actions of cannabis are mediated by receptors that are part of an endogenous cannabinoid system. The endocannabinoid system (ECS) consists of the naturally occurring ligands N-arachidonoylethanolamine (anandamide) and 2-arachidonoylglycerol (2-AG), their biosynthetic and degradative enzymes, and the cannabinoid receptors CB1 and CB2. The ECS is a widely distributed transmitter system that controls gut functions peripherally and centrally. It is an important physiologic regulator of gastrointestinal motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
161
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(163 citation statements)
references
References 121 publications
1
161
0
1
Order By: Relevance
“…2-AG has been previously reported to affect cellular functions in different cell types through a myriad of receptors (Fig. 5A), for example, through engagement of cycloxygenase-2 (COX2) in myeloid cells by the 2-AG hydrolysis product arachidonic acid (10), through peroxisome proliferator-activated receptor a (PPARa) in mesenchymal stem cells (27), and the specific cannabinoid receptors CB1 and CB2 (28). We found that the 2-AGdriven resistive effect on pDC activation could not be reversed by the COX2-specific inhibitor valdecoxib (Fig.…”
Section: -Ag Controls Type I Ifn Induction By Pdcs Through Cb2 Recepmentioning
confidence: 99%
“…2-AG has been previously reported to affect cellular functions in different cell types through a myriad of receptors (Fig. 5A), for example, through engagement of cycloxygenase-2 (COX2) in myeloid cells by the 2-AG hydrolysis product arachidonic acid (10), through peroxisome proliferator-activated receptor a (PPARa) in mesenchymal stem cells (27), and the specific cannabinoid receptors CB1 and CB2 (28). We found that the 2-AGdriven resistive effect on pDC activation could not be reversed by the COX2-specific inhibitor valdecoxib (Fig.…”
Section: -Ag Controls Type I Ifn Induction By Pdcs Through Cb2 Recepmentioning
confidence: 99%
“…In addition, the eCB system plays a crucial role in the regulation of energy balance through central and peripheral mechanisms (Quarta et al . ; Sharkey & Wiley, ). Nutritional status causes dramatic changes in eCB signalling and related synaptic plasticity in brain regions involved in the sensing of nutrient availability.…”
Section: Introductionmentioning
confidence: 97%
“…Among several actors involved in synaptic plasticity, lipid messengers such as endocannabinoid (eCB) are key modulators of synaptic functions (Castillo et al 2012) where they mediate diverse forms of short and long-term changes in synaptic efficacy. In addition, the eCB system plays a crucial role in the regulation of energy balance through central and peripheral mechanisms (Quarta et al 2010;Sharkey & Wiley, 2016). Nutritional status causes dramatic changes in eCB signalling and related synaptic plasticity in brain regions involved in the sensing of nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial properties of cannabinoids on the gastrointestinal (GI) tract are built on the fact that the intestines are endowed with the endocannabinoid system (ECS), a regulatory network of cannabinoid receptors, enzymes, and ligands that play key roles in physiological as well as pathophysiological processes [1][2][3][4]. Thus, the gut expresses the classical cannabinoid receptors 1 and 2 (CB 1 , CB 2 ) and cannabinoid-responsive non-CB 1 /CB 2 receptors (G protein-coupled receptor 55 [GPR55], transient receptor potential cation channel subfamily V member 1 [TRPV1], and peroxisome proliferator-activated receptor gamma and alpha [PPARγ and PPARα]).…”
Section: Introductionmentioning
confidence: 99%